2014
DOI: 10.1371/journal.pone.0108465
|View full text |Cite
|
Sign up to set email alerts
|

Contourlet Textual Features: Improving the Diagnosis of Solitary Pulmonary Nodules in Two Dimensional CT Images

Abstract: ObjectiveTo determine the value of contourlet textural features obtained from solitary pulmonary nodules in two dimensional CT images used in diagnoses of lung cancer.Materials and MethodsA total of 6,299 CT images were acquired from 336 patients, with 1,454 benign pulmonary nodule images from 84 patients (50 male, 34 female) and 4,845 malignant from 252 patients (150 male, 102 female). Further to this, nineteen patient information categories, which included seven demographic parameters and twelve morphologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…When textural features were combined with clinical and CT features, differentiating performance significantly increased from 79 to 92.9% (p < 0.05). As with the previous study, Wang et al 68 showed that TA can improve diagnostic certainty. In contrast to the previous study, this study analysed the whole tumour, instead of a single image slice.…”
Section: Pre-treatment Textural Analysis (Ta)supporting
confidence: 68%
“…When textural features were combined with clinical and CT features, differentiating performance significantly increased from 79 to 92.9% (p < 0.05). As with the previous study, Wang et al 68 showed that TA can improve diagnostic certainty. In contrast to the previous study, this study analysed the whole tumour, instead of a single image slice.…”
Section: Pre-treatment Textural Analysis (Ta)supporting
confidence: 68%
“…These studies used texture analysis with machine learning, 2-or 3-dimensional (3D) convolutional neural network (CNN), residual network, ensemble method, and transfer learning (TL) on CT images to classify lung nodules. [8][9][10][11][12][13][14][15][16][17] The TL method uses an unconnected training set to preconfigure the CNN to reduce the size of the specific training set. 18 It allows more effective learning about new things based on pretrained weights from a large image data set.…”
mentioning
confidence: 99%
“…Recently, several studies using deep learning or machine learning approaches to diagnose lung cancer with conventional CT and FDG PET/CT have been published. These studies used texture analysis with machine learning, 2- or 3-dimensional (3D) convolutional neural network (CNN), residual network, ensemble method, and transfer learning (TL) on CT images to classify lung nodules 8–17 . The TL method uses an unconnected training set to preconfigure the CNN to reduce the size of the specific training set 18 .…”
mentioning
confidence: 99%